Diagnosis and antibacterial treatment for community-acquired pneumonia in children during the COVID-19 pandemic - S.V. Zaitseva; O.V. Zaitseva; E.E. Lokshina (LCC «Medicine-Inform», 2021)
S.V. Zaitseva1,2, O.V. Zaitseva1, E.E. Lokshina1 1A.I. Evdokimov Moscow University of Medicine & Dentistry, Moscow, Russian Federation 2Federal Research Clinical Center for Children and Adolescents of the Federal Medical Biological Agency of Russia, Moscow, Russian Federation During the COVID-19 pandemic, the reasonable use of antibiotics became an important issue of practical health care. This fact is accounted for by the heavy burden of COVID-19 on healthcare system, difficulties with interpreting respiratory disorders and verifying community-acquired pneumonia using instrumental and laboratory tests. Therefore, the risk of unnecessary prescription of antibiotics and, as a result, the prevalence of antibiotic resistance significantly increase. This paper addresses current ideas about the role of the most common causative agents of community-acquired pneumonia in children, the milestones of the diagnosis of community-acquired pneumonia, differential diagnosis of viral and bacterial pneumonia, the algorithms of the choice of basic antibacterial treatment in out-patient settings. The authors emphasize that only the use of limited antibiotic spectrum (i.e., amoxicillin, inhibitor-protected aminopenicillins), their rational dosing and course treatment  recommended for community-acquired pneumonia will prevent the loss of antibacterial efficacy for infectious diseases. Keywords: community-acquired pneumonia, children, SARS-CoV-2, antibiotic therapy, antibiotic resistance, inhibitor-protected aminopenicillins. For citation: Zaitseva S.V., Zaitseva O.V., Lokshina E.E. Diagnosis and antibacterial treatment for community-acquired pneumonia in children during the COVID-19 pandemic. Russian Journal of Woman and Child Health. 2021;4(1):70-76. DOI: 10.32364/2618-8430-2021-4-1-70-76.